Die Erfindung des Vampirs : Mythenbildung zwischen populären Erzählungen vom Bösen und wissenschaftlicher Forschung. - Unterholzner, Bernhard (Harrassowitz Verlag, 2019)
The invention of the vampire begins in 1732 with a media event. Reports about recurring deaths from the Austrian periphery electrified the press market of the Enlightenment. Physicians, philosophers and theologians excitedly discussed the outrageous event and political journalism immediately used the "bloodsucker" as a metaphor for exploitation. A little later the vampire was dismissed as a superstition, but by no means settled. In the long 19th century the vampire was not only in literature and theater and opera, but also in non-fiction publications. Authors from travel literature, folklore, natural philosophy, psychiatry and psychoanalysis created the vampire as an ambiguous figure in their writings: superstition of Eastern Europeans, bat, energy sucker, sadist and lust dream. The cinema added a visual level to these stories "Vampires were from then on visualized. As a reflective figure of borderline states, the vampire remained relevant into the 20th century, before parasites and viruses became the most important metaphors of the other. In The Invention of the Vampire, Bernhard Unterholzner maps the proliferating network of discourse contributions by well-known wi e of forgotten authors that formed the character of the vampire. Gathering great debates and entertaining skirmishes, the book explains how the vampire became the mythical figure we know today.